Epidermal Stem Cells in Hair Follicle Cycling and Skin Regeneration: A View From the Perspective of Inflammation - Morgun, Elena I.; Vorotelyak, Ekaterina A. (Frontiers in Cell and Developmental Biology, 2020)
There are many studies devoted to the role of hair follicle stem cells in wound healing as well as in follicle self-restoration. At the same time, the influence of the inflammatory cells on the hair follicle cycling in both injured and intact skin is well established. Immune cells of all wound healing stages, including macrophages, γδT cells, and Tregs, may activate epidermal stem cells to provide re-epithelization and wound-induced hair follicle neogenesis. In addition to the ability of epidermal cells to maintain epidermal morphogenesis through differentiation program, they can undergo de-differentiation and acquire stem features under the influence of inflammatory milieu. Simultaneously, a stem cell compartment may undergo re-programming to adopt another fate. The proportion of skin resident immune cells and wound-attracted inflammatory cells (e.g., neutrophils and maсrophages) in wound-induced hair follicle anagen and plucking-induced anagen is still under discussion to date. Experimental data suggesting the role of reactive oxygen species and prostaglandins, which are uncharacteristic of the intact skin, in the hair follicle cycling indicates the role of neutrophils in injury-induced conditions. In this review, we discuss some of the hair follicles stem cell activities, such as wound-induced hair follicle neogenesis, hair follicle cycling, and re-epithelization, through the prism of inflammation. The plasticity of epidermal stem cells under the influence of inflammatory microenvironment is considered. The relationship between inflammation, scarring, and follicle neogenesis as an indicator of complete wound healing is also highlighted. Taking into consideration the available data, we also conclude that there may exist a presumptive interlink between the stem cell activation, inflammation and the components of programmed cell death pathways.